Social, educational and vocational outcomes in patients with childhood‐onset and young‐adult‐onset growth hormone deficiency. (3rd February 2017) - Mitra, M. Tanya; Jönsson, Peter; Åkerblad, Ann‐Charlotte; Clayton, Peter; Kołtowska‐Häggström, Maria; Korbonits, Márta; Toogood, Andy; Gleeson, Helena
Summary: Objective: Hypopituitarism diagnosed in childhood, adolescence and young adulthood has the potential to affect growth and somatic development. Less is known about the impact of such a diagnosis on other aspects of development. Design: An analysis of the KIMS database (Pfizer International Metabolic Database) was performed to explore social, educational and vocational outcomes of adult patients diagnosed in childhood, adolescence and young adulthood compared with adult‐onset controls. Patients: A total of 2952 adult patients diagnosed with hypothalamic pituitary conditions before the age of 25 were divided into two groups: childhood‐onset [<16 years (CO)] ( n = 1782) and young‐adult‐onset [16 to <25 years (YAO)] ( n = 1170). A total of 1617 adult patients diagnosed with a nonfunctioning pituitary adenoma at the age of 25 or older formed the adult‐onset control group (AO). Measurements: KIMS Patient Life Situation Form which provided information on social, educational and vocational outcomes. Results: Compared with the AO control group, CO and YAO patients were between 4·5 and 8·0 times more likely to live with their parents in adulthood; CO and YAO patients were also less likely to live in partnership and to have children. The impact on educational and vocational outcomes was less marked than on social outcomes with no significant differences compared with the AO control group. Educational and vocational outcomes showed the lowest level in male and female CO and YAO patients who had been previously diagnosed with a brain tumour. Conclusions: Social outcomes were more affected than educational and vocational outcomes. Although CO patients are more adversely affected, YAO patients were also failing to achieve social milestones. This has consequences for the delivery of endocrine care in both paediatric and adult services.